Traditional wood carving and decorated elements on boats in Terengganu / Nur Irda Suriani Zainal Abiddin - Zainal Abiddin, Nur Irda Suriani (2016)
The purpose of this research is to review the traditional wood carving on boats in Terengganu. In the passage of time this national treasure is becoming endangered and extinct of the world. Time has witnessed that old things perish and will eventually be forgotten. The same is happening to the traditional wood carving features in boats at Terengganu. Most of these attractive and unique carving are deteriorating due to negligence and lack of proper care. Thus, if no immediate action is taken any preserve those, this traditional Malay art will be lost forever. In conjunction, this study is aimed to explore and identify the application of traditional woodcarvings and decorated elements on a boat especially in Terengganu. The objectives of this study are to identify the types of traditional wood carving and decorated elements on boats. The result from this study was documented. This research involves the study of qualitative in which it was conducted by reviewing the literature on the topic, which is includes further studies through the method of observation and interviews. The most important is able to collect samples and left over treasures tradition particularly in the collection of motifs and implicit the message behind each artwork. Traditional boats were observed through a significant change; especially in terms of design where wood carvings are no longer apply. The collected motifs were shown to be an effective way of documented the national treasure of wood carving in each creation of arts before its extinction. Hopefully this research will create an awareness of this need and encourage our young generation to revitalize this fine and high quality works of wood carving.